Multi-temporal analysis of Nouakchott floods (1994–2024) using remote sensing and key hydrological parameters - Aillal, Melainine Mouhcin; Kebd, Sidi Muhamed; Sidina, El Moctar Cheikh Mohamed; Lafdal, Mohamed Yahya (Journal of Water and Land Development, 2026)
The city of Nouakchott has faced a growing incidence of flooding for several decades, exacerbated by climatic, hydrogeological, and anthropogenic factors. This study is based on a multitemporal remote sensing analysis using satellite images from four key years: 1994, 2004, 2014, and 2024. Its objective is to track the spatial and temporal evolution of flooded areas while assessing the hydrological and ecological impacts of these floods on the urban environment. The flood-prone area of the city, assessed at 10-year intervals (1994, 2004, 2014, and 2024), increased from 0.07 to 0.13%, then to 1.05%, and finally to 3.96%, indicating a marked expansion of flood-affected areas over the decades. This historical trend indicates a worsening problem, with flooded areas now nearly 50 times more extensive than in 1994. This observation is supported by analyses of groundwater behaviour, annual precipitation, and soil infiltration capacity. Rising groundwater levels and soil impermeability affect the spread of flooded areas. The study underscores the urgency of implementing sustainable urban planning policies and improving stormwater management to mitigate the ecological and health risks associated with flooding